2018
DOI: 10.1002/acn3.647
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and infarction patterns of PFO‐related cryptogenic strokes and a prediction model

Abstract: ObjectivesThe higher than expected PFO rate in CS patients has raised concerns that paradoxical embolism maybe the pathophysiologic mechanism for strokes. However, only a small proportion of pathogenic PFOs cause CS. Therefore, accurate recognition of patients with pathogenic PFOs among all CS patients could guide clinical decision making in selecting the most appropriate treatment. The aim of this study was to devise a new algorithm to stratify cryptogenic stroke (CS) patients into pathogenic patent foramen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Individuals with migraine are at a higher risk for stroke [18]. Recent studies have demonstrated that PFO is implicated in stroke, especially cryptogenic stroke, and the prevalence of PFO in patients with cryptogenic stroke is much higher than that in the normal healthy population [7]. Transcatheter closure of PFO is superior to medical therapy in reducing the recurrence of stroke [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with migraine are at a higher risk for stroke [18]. Recent studies have demonstrated that PFO is implicated in stroke, especially cryptogenic stroke, and the prevalence of PFO in patients with cryptogenic stroke is much higher than that in the normal healthy population [7]. Transcatheter closure of PFO is superior to medical therapy in reducing the recurrence of stroke [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence is between one-quarter and one-third of individuals [4,5]. Recent studies have confirmed that PFO is a risk factor for cerebral events, such as cryptogenic stroke, transient ischemic attacks (TIA), migraine headaches, and hypoxemia [6][7][8]. PFO may act as the pathway of thrombi from the venous circulation to the cerebral circulation and could cause paradoxical embolisms, even inducing transient arrhythmia, both of which are recognized as potential underlying mechanisms [7,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…It is also known that the maximum blood flow velocity in the IJV is 1/3-1/2 of the peak systolic blood flow velocity (VPS cm/s) by CCA. Knowing the cross-sectional areas of the IJV and CCA, as well as the peak systolic velocity of the CCA in each case, it is possible to determine the "optimal" speed from the IJV and compare it with the actual one using formulas (1) and (2)…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that at present, arterial stroke is quite well studied, approaches to the diagnosis and treatment of 22-30% of cases in its classification are developed and systematized for cryptogenic stroke [1]. Indeed, the etiology of a stroke cannot always be determined, and the cause of its occurrence remains unknown [2][3][4]. Generally, the term "stroke" refers to cerebral artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, PFO is deemed as a significant phenomenon that is highly correlated with migraine headaches, cryptogenic stroke, and other common mental disorders. Hence, more and more studies have focused on PFO-RLS, in terms of RLS-related diseases [ 1 , 2 ]. While in recent years, several studies indicated that other types of RLS, other than PFO-RLS, are not uncommon, with the incidence rate between 20 and 41%.…”
Section: Introductionmentioning
confidence: 99%